QUEUING SYSTEM DESIGN USING WEBSITE TECHNOLOGY - Badawi, Afif; Muslim; Anjasmara, Budi (Cattleya Darmaya Fortuna, 2024)
Queuing systems are an important element in efficient service management, especially in sectors that involve high interaction between customers and service providers. This research aims to design and develop a web-based queuing system to improve queue management efficiency, reduce waiting time, and provide a better user experience. The proposed system utilizes the latest technologies such as modern web frameworks, structured databases, and real-time integration to support flexible and responsive operations. The system design involves queue management modules, real-time monitoring, as well as automatic notifications for users. The implementation results show that this system is able to minimize waiting time, improve queue management accuracy, and provide easy access for users through web-based devices. Thus, this system has the potential to be widely applied in various service sectors, such as banking, hospitals, and other public service centers.